EFFECT OF FEEDING VARIOUS SILAGES AT LATE PREGNANCY OF ETAWAH CROSSBRED DOES ON THE GROWTH OF THEIR KIDS - MAHAYANI N. K. S. P.; L. DOLOKSARIBU; M. DEWANTARI (Majalah Ilmiah Peternakan)
Feeding qualified feeds to late pregnant dairy does is crucial to produce qualified kids as replacement stock. This study was to observe the effects of feeding various silages at late pregnancy on the growth profile of kids of PE does reared in Lemukih Village, Bali. This study was conducted from March until Juli 2023. Randomized block de- sign consisting of four feeding treatments: Forage (T0), Forage+Soybean Husk Silage (SHS) (T1), Forage+Brewer’s Spent Grain Silage (BSGS) (T2), and Forage+Odot Silage (OS) (T3), and three groups of bodyweights of the does were used. The observed parameters: birth weight, weaning weight, and ADG of kids born from each does treat- ment. The results showed birth weights were not significant difference; and kids of T2 does tended to be heavier being 2,878 ± 239.5 g/head. Although birth weight of kids of T1 does tended to be lighter 2,779 ± 221.7 g/head, their weaning weight 10,119 ± 868.7 g/head, and the ADG of the kids 122.3 ±11.8 g/head/day were the heaviest compared to kids of the control does being 5,860 ± 938.3 g and 51.2 ± 12.8 g/head/day, respectively. In summary, feeding SHS improved the growth profile of kids by showing their weaning weight and ADG.